The Differential Role of Executive Apathy in Alzheimer’s Disease Dementia, Mild Cognitive Impairment and Healthy Cognitive Ageing - Michalis Mougias; Ion N. Beratis; Kleio Moustaka; Panagiotis Alexopoulos; Konstantinos Assimakopoulos (Geriatrics, 2023)
The objective of the present work was to compare the levels of executive, emotional, and initiation apathy in individuals with mild cognitive impairment (MCI), mild Alzheimer’s disease dementia (ADD), and cognitively intact healthy controls (HCs). Fifty-two patients with mild ADD, 40 individuals with MCI, and 37 cognitively intact individuals were included in the current study. The participants were consecutive visitors to the Outpatient Memory Clinic of “Nestor” Alzheimer’s Center. The symptoms of apathy were measured with the dimensional apathy scale. Analyses showed that ADD patients had significantly higher degrees of executive, emotional, initiation, and overall apathy compared with both the MCI group and the HCs. Additionally, a significant difference was observed in the dimension of executive apathy between individuals with MCI and the HCs. In conclusion, the dimension of executive apathy was the most sensitive measure regarding the differentiation of individuals with mild ADD or MCI and HCs. Hence, detailed evaluation of executive apathy in older individuals referred to a memory clinic may provide useful information contributing to their diagnostic categorization and to the differentiation between neurocognitive disorders and healthy cognitive ageing.